Innovation Performance in Poland and Polish Companies - Pałubska, Dorota (Comparative Economic Research. Central and Eastern Europe, 2011)
Poland, with its’ weak innovation performance still lags far behind most European countries. The share of expenditures on Research and Development In GDP accounts for 0,56% and represents one of the lowest levels in Europe. It is estimated, that Poland, with its’ current innovation growth rate, will reach the average level of EU in about 20 years. The goal of this paper is to analyse the current innovation situation of Poland's economy and Polish companies in comparison to EU countries. The article presents also results of survey on investing in innovations in large Polish companies.